Globalization and the Philosophy of Community Development in Africa (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2023)
Globalization has been used to describe the revolution that has taken place in information communication technology. This revolution is such that it has influenced and affected different people in different part of the world differently. The concept of community has long been examined by various disciplines such as geography, sociology, psychology and philosophy. The paper therefore takes a look at the philosophy of community development especially as it has evolved in the age of globalization, does the uncertainty and insecurity associated with modernization and globalization still give room to talk about a community even a global community? In essence globalization has brought about a new community philosophy. These new forms of community are based on cultural G attachments, rather than on the innate social orders. This new form distinguishes itself from the traditional concept through its position that the community ties are decreasingly organized within a place. It is a social network that goes beyond geographical boundaries, owing much to developments in the advancement of telecommunication and greater mobility. So, does this mean the end of a place-bound community? In this uncertain, globalized society has the traditional community lost its existence? This paper examines or explores the sense of community in contemporary African state in the age of globalization.